THE ROLE OF TOURISM IN CREATING MENTAL HEALTH AMONG GEN Z IN BATU - Andini Sakti, Aileen; Satrya, I Dewa Gde (Jurnal Bisnis dan Keuangan, 2025)
This study examines the role of tourism in improving mental health, with a focus on its impact on Generation Z in Batu. The COVID-19 pandemic, which has affected the world since early 2020, led to an increase in mental health issues across various groups, particularly among the younger generation. One of the responses to this situation was the growing awareness of the importance of "healing" or mental recovery, which encouraged individuals, especially Generation Z, to seek new ways of coping with stress and anxiety. One increasingly popular approach is traveling, which is believed to offer benefits for mental health. This study aims to explore whether traveling activities have a positive impact on mental health and how tourist destinations and Memorable Travel Experiences (MTE) can contribute to mental recovery. Batu was chosen as the research destination due to its variety of tourist attractions that promote relaxation and recreation. The research methodology used is qualitative, with in-depth interviews as the primary data collection method, as well as secondary data analysis in the form of documentation and interview recordings. The study focuses on the perspectives and experiences of Generation Z regarding traveling as a way to improve their mental health. Based on the findings, traveling activities can serve as an effective means to reduce stress, enhance emotional well-being, and provide individuals with an opportunity for mental recovery. Overall, the results of this study provide deeper insights into the mutually beneficial relationship between the tourism sector and mental health, particularly among Generation Z. Therefore, the tourism sector can play an important role in supporting the psychological well-being of the younger generation by creating experiences that contribute to their mental recovery process.